Study of Bokashi’s Type and Dosages to Growth and Harvest Yield Honey Dews (Cucumis Melo L.) In Low Land - Ana Amiroh (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2016)
Recently, most cultivation and planting of Melon (Cucumis melo L.) by farmers using inorganic fertilizers with an excessive dosage, and this causes the lowland productivity decrease with consequent. The soil organic matter decreased as low as time increasing. Application and using of mature organic matter are an alternative to solve these problems in order the lowland become more conducive and productive for growth of melon. But increasing pests and diseases attaching to the plants may caused by adding immature organic matters into soil. Sources to make bokashi like as paddy straw and water hyacinth is immense but it’s not yet used. This research was aimed to study, know and usage of paddy straw and water hyacinth bokashi’s on melon growing at lowland. Experiment was conducted at Lowland Experiment Station of Agricultural Faculty, Brawijaya, in Jatikerto Village, Kromengan Distric, Malang, from April-June 2015. Experiment was applied in a Randomized Block Design (RBD) with double factors Types and Dosages of Bokashis. There is seven combinations of treatment with three replications, each treatment consisted four individual plants. Result showed there is significant difference between types and dosages of bokashi on plant length at 28, 35, 42 dan 49 days after planting (d,a,p) respectively. The significant difference between treatment also shown by leaf area at 28 - 49 (d.a.p.). Application of paddy straw bokashi was better than hyacinth bokashi on melon growth. The best yield shows that by using paddy straw bokashi with 5 ton/ha of dosage gives melon with 2,56 kg /plant fresh weight.